2008
DOI: 10.1128/mcb.00607-07
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Activation of Histone Genes Requires NPAT-Dependent Recruitment of TRRAP-Tip60 Complex to Histone Promoters during the G1/S Phase Transition

Abstract: Transcriptional activation of histone subtypes is coordinately regulated and tightly coupled with the onset of DNA replication during S-phase entry. The underlying molecular mechanisms for such coordination and coupling are not well understood. The cyclin E-Cdk2 substrate NPAT has been shown to play an essential role in the transcriptional activation of histone genes at the G 1 /S-phase transition. Here, we show that NPAT interacts with components of the Tip60 histone acetyltransferase complex through a novel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 68 publications
2
66
0
Order By: Relevance
“…53,54 Hence, the outcome of the recruitment of transcriptional (co)factors, histone modifications included, is dependent upon genomic targets (contexts) as exemplified by our studies, the underlying mechanism certainly deserves further investigation.…”
Section: Discussionmentioning
confidence: 75%
“…53,54 Hence, the outcome of the recruitment of transcriptional (co)factors, histone modifications included, is dependent upon genomic targets (contexts) as exemplified by our studies, the underlying mechanism certainly deserves further investigation.…”
Section: Discussionmentioning
confidence: 75%
“…However, we showed here that the interaction of FLASH with ARS2, not NPAT, is necessary for S phase progression. Moreover, although NPAT was reported to be required for S phase entry (7,19,27,29,30), FLASH, ARS2 and their interaction are necessary for S phase progression but not S phase entry (Fig. 1C, 4F, and 7F).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, these reports indicated that FLASH interacts with a nuclear protein, ataxia-telangiectasia locus (p220 NPAT [NPAT]), a component of Cajal bodies. The phosphorylation of NPAT by cyclin E/Cdk2 was reported to regulate the activation of histone gene transcription in S phase and to be necessary to maintain the structure of Cajal bodies during the cell cycle (7,19,27,29,30). Therefore, FLASH has been thought to play an essential role in S phase progression, probably through interaction with NPAT.…”
mentioning
confidence: 99%
“…NPAT functions, in part, by recruiting coactivator proteins including histone-modifying enzymes (DeRan et al, 2008). Moreover, NPAT transcription is regulated in a cell cycle-dependent manner by the E2F family of transcription factors (Gao et al, 2003).…”
Section: Introductionmentioning
confidence: 99%